Assessment and longitudinal analysis of health impacts and stressors perceived to result from unconventional shale gas development in the Marcellus Shale region. (June 2013) - Ferrar, Kyle J; Kriesky, Jill; Christen, Charles L; Marshall, Lynne P; Malone, Samantha L; Sharma, Ravi K; Michanowicz, Drew R; Goldstein, Bernard D
Abstract : Introduction: Concerns for health and social impacts have arisen as a result of Marcellus Shale unconventional natural gas development. Our goal was to document the self-reported health impacts and mental and physical health stressors perceived to result from Marcellus Shale development. Methods: Two sets of interviews were conducted with a convenience sample of community members living proximal to Marcellus Shale development, session 1 March–September 2010 ( n  = 33) and session 2 January–April 2012 ( n  = 20). Symptoms of health impacts and sources of psychological stress were coded. Symptom and stressor counts were quantified for each interview. The counts for each participant were compared longitudinally. Results: Participants attributed 59 unique health impacts and 13 stressors to Marcellus Shale development. Stress was the most frequently-reported symptom. Over time, perceived health impacts increased ( P  = 0·042), while stressors remained constant ( P  = 0·855). Discussion: Exposure-based epidemiological studies are needed to address identified health impacts and those that may develop as unconventional natural gas extraction continues. Many of the stressors can be addressed immediately.